ANALYSIS OF TESTING RESULTS OF LIQUID SAMPLES FROM DRILLING WELLS IN OIL AND GAS INDUSTRY - Achmad Faisal Faputri; Indah Agus Setiorini (Jurnal Ilmiah Hospitality, 2022)
In crude oil and petroleum products the presence of water must be removed because water is included in the category of impurities. The more impurities contained in petroleum products, the lower the quality and quality of the product. The main reason why water cannot be tolerated in petroleum products is that water can cause heat surges and pressure in the crude distillation unit will increase, and result in sub-optimal processing. The purpose of this study was to determine the amount of water content in a mixture of liquid samples from drilling wells at PT. X. From the results of research analysis using the ASTM D-95 water content test parameter, it shows that the largest water content is in the JRK-217/SP4 sample, which is 14.5% Vol, while the smallest water content is in the JRK-123/SP5 and JRK-132 samples. /SP5 which is equal to 0.00% Vol.